Is Video-Based Education an Effective Method in Surgical Education? A Systematic Review - Ahmet, Akgul; Gamze, Kus; Rustem, Mustafaoglu; Sezen, Karaborklu Argut (Journal of surgical education, 2018)
Visual signs draw more attention during the learning process. Video is one of the most effective tool including a lot of visual cues. This systematic review set out to explore the influence of video in surgical education. We reviewed the current evidence for the video-based surgical education methods, discuss the advantages and disadvantages on the teaching of technical and nontechnical surgical skills. This systematic review was conducted according to the guidelines defined in the preferred reporting items for systematic reviews and meta-analyses statement. The electronic databases: the Cochrane Library, Medline (PubMED), and ProQuest were searched from their inception to the 30 January 2016. The Medical Subject Headings (MeSH) terms and keywords used were “video,” “education,” and “surgery.” We analyzed all full-texts, randomised and nonrandomised clinical trials and observational studies including video-based education methods about any surgery. “Education” means a medical resident’s or student’s training and teaching process; not patients’ education. We did not impose restrictions about language or publication date. A total of nine articles which met inclusion criteria were included. These trials enrolled 507 participants and the total number of participants per trial ranged from 10 to 172. Nearly all of the studies reviewed report significant knowledge gain from video-based education techniques. The findings of this systematic review provide fair to good quality studies to demonstrate significant gains in knowledge compared with traditional teaching. Additional video to simulator exercise or 3D animations has beneficial effects on training time, learning duration, acquisition of surgical skills, and trainee’s satisfaction. Video-based education has potential for use in surgical education as trainees face significant barriers in their practice. This method is effective according to the recent literature. Video should be used in addition to standard techniques in the surgical education.